Baseline sensorimotor GABA levels shape neuroplastic processes induced by motor learning in older adults. Issue 13 (25th June 2020) - King, Bradley R.; Rumpf, Jost‐Julian; Verbaanderd, Elvire; Heise, Kirstin F.; Dolfen, Nina; Sunaert, Stefan; Doyon, Julien; Classen, Joseph; Mantini, Dante; Puts, Nicolaas A. J.; Edden, Richard A. E.; Albouy, Geneviève; et al.
Abstract: Previous research in young adults has demonstrated that both motor learning and transcranial direct current stimulation (tDCS) trigger decreases in the levels of gamma‐aminobutyric acid (GABA) in the sensorimotor cortex, and these decreases are linked to greater learning. Less is known about the role of GABA in motor learning in healthy older adults, a knowledge gap that is surprising given the established aging‐related reductions in sensorimotor GABA. Here, we examined the effects of motor learning and subsequent tDCS on sensorimotor GABA levels and resting‐state functional connectivity in the brains of healthy older participants. Thirty‐six older men and women completed a motor sequence learning task before receiving anodal or sham tDCS to the sensorimotor cortex. GABA‐edited magnetic resonance spectroscopy of the sensorimotor cortex and resting‐state (RS) functional magnetic resonance imaging data were acquired before and after learning/stimulation. At the group level, neither learning nor anodal tDCS significantly modulated GABA levels or RS connectivity among task‐relevant regions. However, changes in GABA levels from the baseline to post‐learning session were significantly related to motor learning magnitude, age, and baseline GABA. Moreover, the change in functional connectivity between task‐relevant regions, including bilateral motor cortices, was correlated with baseline GABA levels. These data collectively indicate that motor learning‐related decreases in sensorimotor GABA levels and increases in functional connectivity are limited to those older adults with higher baseline GABA levels and who learn the most. Post‐learning tDCS exerted no influence on GABA levels, functional connectivity or the relationships among these variables in older adults. Abstract : Gamma‐aminobutyric acid (GABA)‐edited magnetic resonance spectroscopy of the sensorimotor cortex and resting‐state (RS) functional magnetic resonance imaging data were acquired before and after a motor learning task and either anodal or sham transcranial direct current stimulation (tDCS). Results demonstrated that neither motor sequence learning nor subsequent tDCS significantly modulated GABA+ levels or RS functional connectivity at the group level in older adults. However, individual differences in the learning‐related modulations in GABA+ levels were associated with the participants' age, baseline GABA+ levels, and the magnitude of learning. Higher baseline GABA was also linked to a learning‐related increase in RS functional connectivity between motor task‐relevant regions, including bilateral motor cortices.